2009
DOI: 10.2116/analsci.25.333
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Separation of Proteins in Capillaries Filled with Poly(ethylene oxide)-stabilized Silver Nanoparticles

Abstract: Poly(ethylene oxide)-stabilized silver nanoparticles (PEO-SSNPs) were synthesized and investigated for their potential use in capillary electrophoretic separation of proteins. It was found that the PEO-SSNPs were relatively stable against changes of the buffer ionic strength, while they began to aggregate with increase of buffer pH. Adding 0.024 g/L PEOSSNPs to 30 mmol/L phosphate buffer (pH 2.66) led to obvious increase in the peak heights of albumin bovine and albumin egg. Also, the separation efficiency for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…80 Some research groups have reported the use of AgNPs as the matrix and affinity probes, 81,82 as preconcentrating supports 83 or as an effective pseudostationary phase for CE. 84 However, their extensive utilization in analytical applications requires further exploration. To couple the specic features of AgNPs with monoliths, monolithic columns with embedded AgNPs were developed and tested.…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…80 Some research groups have reported the use of AgNPs as the matrix and affinity probes, 81,82 as preconcentrating supports 83 or as an effective pseudostationary phase for CE. 84 However, their extensive utilization in analytical applications requires further exploration. To couple the specic features of AgNPs with monoliths, monolithic columns with embedded AgNPs were developed and tested.…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…Therefore, the mobilities of target analytes as well as EOF can be controlled and afford an enhanced selectivity and column efficiency. Nanoparticles consisting of gold [], silver [], silica [], titanium dioxide [], polymer [], lipids [], as well as CNT and nanohorns [] have been added to the background electrolyte and used in different capillary electrophoretic modes, such as capillary zone electrophoresis (CZE), electrokinetic chromatography (EKC), micellar electrokinetic chromatography (MEKC), microemulsion electrokinetic chromatography, and CEC. The great potential of nanoparticles contained in running buffers has been demonstrated by efficient separation of proteins [], biologically active amines [], aromatic acids [], pharmaceuticals [], plant hormones [], vitamins [], neutral steroids [], purine and pyrimidine bases [], and nucleotides [].…”
Section: Application Of Nanostructures In Separation Sciencementioning
confidence: 99%
“…For instance, silver nanoparticles [28] and silica nanoparticles [27] have been used for separation of proteins in PSP-CEC. The applications of silver nanoparticles are shown in Fig.…”
Section: From Low-molecular-weight Compounds Toward Protein Separationmentioning
confidence: 99%
“…Since then, the major part of work has focused on analysis of low-molecular-weight compounds [15][16][17]. However, there are some examples of separation of high molecular weight compounds, such as DNA [18][19][20][21] and proteins [22][23][24][25][26][27][28]. Conventional DNA separations in CE based on physical polymer gels are limited by the high viscosity of the polymer solution, which makes replenishment cumbersome.…”
Section: Introductionmentioning
confidence: 99%